Synthesis of nitrogen-doped carbon cellular foam with ultra-high rate capability for supercapacitors. Issue 14 (19th February 2015) - Du, Zhiling; Peng, Youshun; Ma, Zhipeng; Li, Chunying; Yang, Jing; Qin, Xiujuan; Shao, Guangjie
<x xml:space="preserve">Abstract</x> Three-dimensional (3D) interconnected N-doped porous carbons (NPCs) with different levels of pore structure are synthesized by a template method using MnOx as template and N-enriched pyrrole as carbon source.